Genetics of idiopathic ventricular fibrillation. (19th May 2022) - Pannone, L; Gauthey, A; Sorgente, A; Monaco, C; Bisignani, A; Overeinder, I; Bala, G; Almorad, A; Stroker, E; Pappaert, G; Sieira, J; Brugada, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Idiopathic ventricular fibrillation (IVF) accounts for up to 44% of sudden cardiac deaths (SCD); the diagnostic yield of genetic testing in probands is reported as low as 3%. Purpose: The aim of this study is to describe the results of genetic testing in IVF from a high-volume center. Methods: All consecutive patients with IVF and genetic testing were retrospectively analyzed. IVF was diagnosed, following HRS/EHRA guidelines, by means of excluding other causes through clinical, imaging and genetic data. Genetic analysis was performed in all patients with SeqCap v3 for Brugada syndrome and with next generation sequencing HiSeq1500 for other inherited primary arrhythmia syndromes. Genetic variants were classified following ACMG as pathogenic (P)/likely pathogenic (LP) or variants of unknown significance (VUS). Results: Fourteen patients with IVF were included (Table); an ICD was implanted in all patients. A genetic variant was found in 9 patients (64.3%), 5 patients with a P/LP variant (35.7%) and 4 patients (28.6%) with a VUS variant. Genes mutated with a P/LP variant included: RYR2 in 3 patients and TTN in 2 patients. Genes mutated with a VUS included: MYPN in one patient, SCN4A in one patient, DES in one patient and CACNA1C in one patient. At a mean follow-up of 76 months 5 patients (35.7%) experienced an ICD shock [2 patients (40%) with P/LP variant vs 3 patients (33%) of VUS/no variants, p=NS). Conclusion: Genetic testing can be useful in IVF; prognosis is modest with a high rate of ICD shock at long-term follow up.